Complete genome sequence of Brachyspira murdochii type strain (56-150T). Issue 3 (May 2010) - Pati, Amrita; Sikorski, Johannes; Gronow, Sabine; Munk, Christine; Lapidus, Alla; Copeland, Alex; Glavina Del Tio, Tijana; Nolan, Matt; Lucas, Susan; Chen, Feng; Tice, Hope; Cheng, Jan-Fang; et al.
Abstract Brachyspira murdochii Stantonet al. 1992 is a non-pathogenic, host-associated spirochete of the familyBrachyspiraceae . Initially isolated from the intestinal content of a healthy swine, the 'group B spirochaetes' were first described asSerpulina murdochii . Members of the familyBrachyspiraceae are of great phylogenetic interest because of the extremely isolated location of this family within the phylum 'Spirochaetes '. Here we describe the features of this organism, together with the complete genome sequence and annotation. This is the first completed genome sequence of a type strain of a member of the familyBrachyspiraceae and only the second genome sequence from a member of the genusBrachyspira . The 3, 241, 804 bp long genome with its 2, 893 protein-coding and 40 RNA genes is a part of theG enomic E ncyclopedia of B acteria and A rchaea project.